Surge arresters. Glossary of terms and definitions from IEC publications 60099-1, 60099-4, 60099-6, 61643-1, 61643-12, 61643-21, 61643-311, 61643-321, 61643-331 and 61643-341 Part 7, (9th July 2004) - British Standards Institution,
No abstract available